2020
DOI: 10.1080/10942912.2020.1742735
|View full text |Cite
|
Sign up to set email alerts
|

A novel application of terpene compound α-pinene for alternative use of sulfur dioxide-free white wine

Abstract: Sulfur dioxide is widely used as a preservative in winemaking owing to its antioxidant and antimicrobial properties. However, it exerts adverse effects on health, causing dermatitis, urticaria, angioedema, diarrhea, and abdominal pain. In the present study, we used α-pinene, which is a fragrant monomeric compound derived from fruit-aroma compounds, as an alternative for SO 2 in white wine fermentation. Three concentrations of αpinene, 0.03125 g/100 mL, 0.0625 g/100 mL, and 0.125 g/100 mL were used. White wine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A particular feature in the chemical profile of this EO was the presence of the monoterpene α−pinene as its major component (38.65% of the total oil composition). This monoterpene is listed by the US Food and Drug Administration among the food additives permitted for direct addition to food for human consumption, and also has been considered as a potentially useful natural antibacterial preservative as an alternative for SO 2 in winemaking [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A particular feature in the chemical profile of this EO was the presence of the monoterpene α−pinene as its major component (38.65% of the total oil composition). This monoterpene is listed by the US Food and Drug Administration among the food additives permitted for direct addition to food for human consumption, and also has been considered as a potentially useful natural antibacterial preservative as an alternative for SO 2 in winemaking [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anise is a plant native to the Middle East that has been used since ancient Egypt, and its major volatile compound is anethol, which is responsible for aniseed's fragrant characteristics [29,48,49]. Anethol was found in very high concentration in Limnos samples, followed by aniseed Muscat samples from Macedonia, while estragole, menthol, 4-anisaldehyde, p-anisaldehyde diethyl acetal, alpha-himachalene, gamma- o-Cymene [34,40,41], alpha-pinene [42][43][44], beta-myrcene [21], D-limonene [21,45], ylangene [18,29], alpha-cedrene [46] and alpha-terpinene [14,29] were detected mostly in Muscat, Muscat of Alexandria and Merlot wines, grape musts, and spirits, as they are characteristic metabolites of these cultivar grapes; however, in this study, their concentration was found to be over 50-fold higher in some Muscat grape marc spirit samples originated from Macedonia. Caryophyllene has been previously found in Cabernet Sauvignon berries [47], while Garcia-Martin et al [35] found terpenols in orujo samples and Giannetti et al [14] and Lukic et al [19] detected terpenes, such as alpha-terpinene, p-cymene, alpha-cubebene, and alpha-calacorene in several European spirit samples.…”
Section: Identification Of Volatile Metabolites In Analyzed Grape Mar...mentioning
confidence: 99%
“…ABTS and potassium persulfate were mixed 1:1 in a dark environment, oxidized for 12 h (marked as ABTS stock solution), and diluted to 0.7 ± 0.02 at OD 734 before use. In a 96-well plate, 20 µL of sample and 180 µL of ABTS solution were mixed, incubated for 6 min in a dark room, and the absorbance was measured at 734 nm, and calculated to Trolox equivalent antioxidant capacity (TEAC) and present as Trolox equivalent (µg/g) [18].…”
Section: Abts Activitymentioning
confidence: 99%